Antinociceptive effect of 3-(2, 3 dimethoxyphenyl)-1(methylfuran-2-yl) prop-2-en-1-one in mice and its mechanisms of action - Ismail, Nur Izzati (2015)
The objective of the present study is to evaluate the antinociceptive activity of the new chalcone derivative, the 3-(2,3 dimethoxyphenyl)-1 (methylfuran-2-yl) prop-2- en-1-one (DMPF), using the chemical- and thermal-induced nociception test together with the mechanisms of actions. It was demonstrated that, administration of DMPF given by the i.p route produced a significant dose-dependent inhibition on acetic acidinduced writhing test, increased in response latency time for the hot plate test and reduction in time spent licking the injected paw for both neurogenic and inflammatory phases in formalin-induced paw licking test. Furthermore, the antinociceptive effect of DMPF in the acetic acid-induced writhing and the hot plate test was not reversed by non-selective opioid receptor antagonist, naloxone, that shown the non-involvement of the opioidergic system in antinociceptive activity of DPMF. Contrarily, administration of DMPF produced significant dose-dependent inhibition in capsaicin-induced paw licking test, glutamate-induced paw licking test, and PMA-induced paw licking test proven the involvement of TRPV1 receptor, glutamatergic system and PKC system. Antinociception caused by DPMF in the acetic acid test reversed the treatment with LNOARG (nitric oxide synthase inhibitor) and charybdotoxin (a large-conductance ca2+-sensitive K+ channels blocker). However, antinociception of DPMF was enhanced by ODQ (a specific guanylyl cyclase inhibitor). To sum up, the results indicate that DPMF produced pronounced central and peripheral antinociception by inhibition on glutamate receptors, TRPV1 receptors and protein kinase C. It is also strongly suggested that the L-arginine/NO/cGMP/BKca channel pathway plays a significant role in DPMF-induced antinociception.